Pembrolizumab Plus Chemotherapy or Anlotinib vs. Pembrolizumab Alone in Patients With Previously Treated EGFR-Mutant NSCLC - Chen, Ya; Yang, Zhengyu; Wang, Yanan; Hu, Minjuan; Zhang, Bo; Zhang, Yanwei; Qian, Fangfei; Zhang, Wei; Han, Baohui (Frontiers in Oncology, 2021)
Objectives: More and more encouraging evidence revealed that immunotherapy could improve clinical outcomes in patients with previously treated non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) variations. However, immunotherapy is still a controversy for NSCLC patients with EGFR mutation. Method: In this retrospective analysis, we compared the clinical efficacy of pembrolizumab monotherapy (PM), pembrolizumab combined with chemotherapy (P+C) and pembrolizumab combined with anlotinib (P+A) in NSCLC patients with EGFR mutation who had failed on EGFR-TKI and platinum-based chemotherapy. Result:Eighty-six patients were included in this study. The overall median progression free survival (PFS) was 3.24 months. Multivariate analysis suggested that EGFRL858R and combined therapy were positive prognostic factors of PFS. The overall median OS was 12.28 months. Multivariate analysis found that high PD-L1 expression (≥50%) and combined therapy seemed to be positive prognostic factors of OS. Among the population, 32 patients received PM, 26 patients received P+C and 28 patients received P+A. Up to Jan 30, 2021, the median PFS of PM, P+C and P+A were 1.50, 4.30 and 3.24 months, respectively. The median OS were 7.41, 14.92 and 15.92 months, respectively. The ORR were 3.1%, 23.1% and 21.4%. Conclusion: Pembrolizumab plus chemotherapy or antiangiogenic therapy significantly prolonged PFS, OS and ORR compared with pembrolizumab alone in our study. EGFRL858R might be a positive prognostic factor of PFS and high PD-L1 expression might be a positive prognostic factor of OS.